Coaching de carreira: análise de uma intervenção em um grupo de alunos de graduação - Stachiu, Mariana (2013)
This article presents the analysis of the initial interviews with a group of students of a private higher education institution, located in Curitiba / PR . The analysis focused on the issues of perspective that students have regarding their employability and professional career. These interviews prior an intervention group in which some of the students who participated answered interviews. The intervention occurred through the use of coaching methodology and epistemology of community social psychology . Twelve students participated in the interviews, the courses of administration, accounting, psychology and physiotherapy from different periods and ages, who volunteered to participate on. The interviews were conducted, consisting of 19 questions. The responses from the interviews were transcribed and linked to the categories: (a) vocational choice, (b) perceptions of the labor market, (c) employability, (d) life project , and (e) preparation for the job market. Content analysis was used as a form of assessment. It was observed that students know 9 little about the subject employability and seek to develop their career through studies, contact with other people, languages and professional courses, practical experiences, such as internships, and seek to improve their personal skills and competencies. Thinking about career and professional future generates contradictions in students. Some feel anxiety and anguish and others have feelings of happiness and achievement. The professional future is now thought, however inarticulate with reality and concrete plans.